Evaluation of binge eating during and after Ramadan (Research, Society and Development, 2024)
Eating behavior has changed significantly over the years, as evidenced by the presence of eating disorders in today's society, such as Binge Eating Disorder (BED). Furthermore, with globalization, religious rites have been affected, such as Ramadan, which can be associated with episodes of binge eating. This study aimed to analyze binge eating during and after Ramadan. The methodology was based on original publications published between 2014 and 2024 to analyze the food consumption of Ramadan practitioners, as well as the circadian differences during this 40-day period and the main determinants of binge eating disorder. From this, the narrative literature review included 79 articles. The databases used were Google Scholar, EBSCO host, SciELO, and PUBMED. After analyzing the articles, exclusion criteria were established, consisting of articles that deviated from the topic, had no relation to fasting or Ramadan, or were outside the expected date range. In conclusion, it was understood that Binge Eating Disorder is not present during the period of religious fasting and that the course and implications of Ramadan depend on the lifestyle of each participating individual.